Nanomaterial based therapeutic approach with bovine colostrums for the skin wound management in experimental model of rats (Acta Scientiarum. Biological Sciences, 2025)
Effective management of burn wounds is crucial for optimal healing, infection prevention, and pain relief. This study blends Bovine colostrum (BC) with Silver Nanoparticles (AgNPs) to create a specialized gel for burn wound care. The primary objective was to evaluate the efficacy of a gel containing 10% BC-loaded AgNPs in treating burn wounds, including wound healing, pain alleviation, infection prevention, and inflammation reduction. UV spectroscopy and zeta sizer were employed to analyze the AgNPs. An absorption peak at 300–400 nm indicated AgNPs formation, with an average size of 243.9 nm confirmed as nanoparticles. Infrared spectroscopy analysis showed distinct peaks representing carbohydrates, lipids, and proteins in the gel. The 10% AgNPs loaded BC gel accelerated wound healing, outperforming NanoColl by day 20. It also reduced oxidative stress, as evidenced by decreased thiobarbituric acid reactive substances (TBARS) and white blood cell counts (WBC). 10% BC gel demonstrates significant promise for burn wound care, as it effectively accelerates the healing process, provides relief from pain, prevents infections, and reduces inflammation.